Morphology-based realization of a rapid scoliosis correction simulation system. (1st March 2018) - Shao, Kun; Wang, Hao; Li, Bingnan; Tian, Dasheng; Jing, Juehua; Tan, Jieqing; Huo, Xing
Abstract: Objective: Scoliosis is a complex spinal deformity in 3D space that commonly occurs in teenagers, especially teenage girls, and judging the actual deformed spine situation using only CT images is difficult. However, using 3D finite element models to help doctors analyse the deformed spine is also time-consuming and laborious. Therefore, software that can quickly and easily perform scoliosis correction analysis is needed. To achieve rapid preoperative simulation of scoliosis correction in 3D space and help doctors construct surgical programmes faster, a morphology-based system was developed for simulating scoliosis correction performance. Methods: The simulation system first takes advantage of the centre point of each vertebra on the entire spine model to fit a space curve. Then the system obtains information from the models and the space curve, and finally, uses the information to simulate scoliosis correction. The deformed spine model in the system can be corrected to a better state. Results: During the simulation process, doctors can easily and clearly see how the vertebral models move, and the deformed spine parameters are also updated and shown. Using this system, doctors can easily simulate scoliosis correction according to their experience and quickly construct a surgical programme. Conclusions: The experimental results show that this system is capable of simulating scoliosis correction according to a doctor's own experience to speed up the operation and provides a scientific basis for the development of surgical programmes. Graphical abstract: Highlights: Applying the knowledge of space geometry to the correction of scoliosis. Correction simulation totally based on the spinal morphology. Rapid support for the correction of scoliosis surgery. Automatic correction simulation controlled by doctors themselves. A highly visualized process of simulation of scoliosis correction.